2021
DOI: 10.15252/embj.2021108050
|View full text |Cite
|
Sign up to set email alerts
|

A small peptide inhibits siRNA amplification in plants by mediating autophagic degradation of SGS3/RDR6 bodies

Abstract: Selective autophagy mediates specific degradation of unwanted cytoplasmic components to maintain cellular homeostasis. The suppressor of gene silencing 3 (SGS3) and RNA‐dependent RNA polymerase 6 (RDR6)‐formed bodies (SGS3/RDR6 bodies) are essential for siRNA amplification in planta. However, whether autophagy receptors regulate selective turnover of SGS3/RDR6 bodies is unknown. By analyzing the transcriptomic response to virus infection in Arabidopsis, we identified a virus‐induced small peptide 1 (VISP1) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…To complete the effector phase of antiviral RNA silencing, RISCs target vsiRNA or miRNA complementary mRNAs and trigger their PTGS via endonucleolytic cleavage or translational inhibition (Waterhouse and Helliwell 2003;Brodersen et al 2008;Carbonell and Carrington 2015;Mengistu and Tenkegna 2021). For the amplification of antiviral RNA silencing, AGOsliced products serve as templates for RdRp (RDR for cellular RdRps) complexes using RNA-helicases (SGS3 and SDE5), the cofactors of RDR-mediated pathways (Vaucheret 2006;Jauvion et al 2010;Csorba et al 2015;Tong et al 2021).…”
Section: The Mechanism and Localization Of Antiviral Rna Silencingmentioning
confidence: 99%
“…To complete the effector phase of antiviral RNA silencing, RISCs target vsiRNA or miRNA complementary mRNAs and trigger their PTGS via endonucleolytic cleavage or translational inhibition (Waterhouse and Helliwell 2003;Brodersen et al 2008;Carbonell and Carrington 2015;Mengistu and Tenkegna 2021). For the amplification of antiviral RNA silencing, AGOsliced products serve as templates for RdRp (RDR for cellular RdRps) complexes using RNA-helicases (SGS3 and SDE5), the cofactors of RDR-mediated pathways (Vaucheret 2006;Jauvion et al 2010;Csorba et al 2015;Tong et al 2021).…”
Section: The Mechanism and Localization Of Antiviral Rna Silencingmentioning
confidence: 99%
“…Li and co-workers reported that geminiviruses appear to indirectly utilize the plant endogenous RNA silencing suppressor calmodulin-like protein (CaM) to inhibit the siRNA mechanism by promoting the autophagic degradation of SGS3 (Figure 2) Li et al, 2017). Recently, Tong et al (2021) identified a novel 71-amino acid virus-induced small peptide (VISP1) in plants that acts as an autophagy cargo receptor. VISP1 overexpression induces selective autophagy, which attenuates SGS3/ RDR6-dependent viral siRNA amplification and enhances viral infection; meanwhile, VISP1 mutants display the opposite effect.…”
Section: Plant Viruses Manipulate Autophagy To Counteract Host Antiviral Defensesmentioning
confidence: 99%
“…Li and co-workers reported that geminiviruses appear to indirectly utilize the plant endogenous RNA silencing suppressor calmodulin-like protein (CaM) to inhibit the siRNA mechanism by promoting the autophagic degradation of SGS3 ( Figure 2 ) ( Li et al., 2014 ; Li et al., 2017 ). Recently, Tong et al. (2021) identified a novel 71-amino acid virus-induced small peptide (VISP1) in plants that acts as an autophagy cargo receptor.…”
Section: Autophagy Is Manipulated By Virusesmentioning
confidence: 99%
“…In Arabidopsis , a small 71 amino acid peptide, VISP1, can be induced by Cucumber mosaic virus (CMV) infection and interacts with ATG8 through UIM (ubiquitin-interacting motif) motif. VISP1 functions as a selective autophagy receptor involved in degradation of SGS3 (suppressor of gene silencing 3)/RDR6 (RNA-dependent RNA polymerase 6)-bodies to negatively regulate siRNA amplification, resulting in suppression of antiviral immunity ( Tong et al, 2021 ).…”
Section: Regulation Of Autophagy By Biotic Stress Signalsmentioning
confidence: 99%